Fast Ripples as a Biomarker of Epileptogenic Tuber in Tuberous Sclerosis Complex Patients Using Stereo-Electroencephalograph - Wang, Yangshuo; Yuan, Liu; Zhang, Shaohui; Liang, Shuangshuang; Yu, Xiaoman; Liu, Tinghong; Yang, Xiaofeng; Liang, Shuli (Frontiers in Human Neuroscience, 2021)
Objectives: The purpose of this study is to evaluate the value of fast ripples (FR) (200-500Hz) recorded by stereo-electroencephalograph (SEEG) in the localization of epileptogenic tubers in tuberous sclerosis complex (TSC) patients. Methods: Seventeen TSC patients with SEEG examination and undergone epileptic surgery were retrospectively enrolled, and were divided into two groups according to the seizure control at one-year post-operative follow-up. The occurrence frequencies of FRs were automatically counted, and the FRs rate was calculated. The high FRs rate was defined as FRs rate≧0.5. According to different positions, the contacts’ locations were divided into three groups: inner of tuber, the junction area of tuber, and out of tuber. The influence factors of postoperative seizure freedom were also analyzed. Results: Twelve patients reached seizure-free after one-year follow-up. FRs were totally found in 24.2% contacts and 67.1% tubers in all assessed patients. There were 1944 contacts in total. 47 contacts with high FRs rate were localized in the junction area of tubers, which was 62.7% of the total number of 75 contacts with high FRs rate, and was 8.4% of total 561 contacts localized in junction area of tubers. Total removal of epileptogenic tubers and total resection of tubers/contacts with high FRs rate were associated with post-operative seizure freedom (P<0.05). Conclusions: FRs were extensively recorded in TSC patients using SEEG, and high FRs rate were mostly detected in the junction area of the epileptogenic tuber, which could aid in the confirmation of epileptogenic tubers.